2019
DOI: 10.1186/s12974-019-1650-x
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal inflammation changes the balance of TNF signalling in cortical grey matter in multiple sclerosis

Abstract: BackgroundRecent studies of cortical pathology in secondary progressive multiple sclerosis have shown that a more severe clinical course and the presence of extended subpial grey matter lesions with significant neuronal/glial loss and microglial activation are associated with meningeal inflammation, including the presence of lymphoid-like structures in the subarachnoid space in a proportion of cases.MethodsTo investigate the molecular consequences of pro-inflammatory and cytotoxic molecules diffusing from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 63 publications
7
103
0
1
Order By: Relevance
“…We suggest that a higher level of demyelination and axonal loss in MS cases expressing meningeal lymphoid-like structures may in part be related to the increased immune cell infiltration in the cord meninges, which via the production of pro-inflammatory cytokines and chemokines, including TNF, IL6, IFNγ and CXCL13, could cause direct and/ or indirect damage to the underlying tissues (18,28,37,38). This inflammatory milieu is reflected in the CSF (27) and a small number of inflammatory mediators, including B cell chemokines, define both a post-mortem and a clinical cohort with a higher lesion load and poor prognosis (38).…”
Section: B Cells and Not T Cells Are Most Strongly Associated With Spmentioning
confidence: 99%
“…We suggest that a higher level of demyelination and axonal loss in MS cases expressing meningeal lymphoid-like structures may in part be related to the increased immune cell infiltration in the cord meninges, which via the production of pro-inflammatory cytokines and chemokines, including TNF, IL6, IFNγ and CXCL13, could cause direct and/ or indirect damage to the underlying tissues (18,28,37,38). This inflammatory milieu is reflected in the CSF (27) and a small number of inflammatory mediators, including B cell chemokines, define both a post-mortem and a clinical cohort with a higher lesion load and poor prognosis (38).…”
Section: B Cells and Not T Cells Are Most Strongly Associated With Spmentioning
confidence: 99%
“…First evidence of the involvement of TNF in the neuroinflammatory process occurring in MS were provided by post mortem studies in MS patients, showing high cytokine levels in close proximity to active CNS lesions [ 12 , 88 , 150 , 151 ]. Moreover, transcriptional analysis of cortical gray matter (GM) tissues of PMS subjects showed the upregulation of both TNFR1 and TNFR2 [ 152 ]. Further immunocytochemical characterizations have shown that TNFR1 is mainly expressed by neurons and oligodendrocytes, while TNFR2 is mostly expressed by microglia and astrocytes in cortical GM [ 152 ].…”
Section: Evidence For Tnf Involvement In Pathological Hallmarks Ofmentioning
confidence: 99%
“…Moreover, transcriptional analysis of cortical gray matter (GM) tissues of PMS subjects showed the upregulation of both TNFR1 and TNFR2 [ 152 ]. Further immunocytochemical characterizations have shown that TNFR1 is mainly expressed by neurons and oligodendrocytes, while TNFR2 is mostly expressed by microglia and astrocytes in cortical GM [ 152 ]. However, the higher expression of genes linked to TNFR1-mediated necroptosis, a different form of necrotic cell death, suggested the prevalence of such TNF-mediated destructive pathway [ 152 ].…”
Section: Evidence For Tnf Involvement In Pathological Hallmarks Ofmentioning
confidence: 99%
“…The understanding of such opposing effects of TNF on oligodendrocytes [ 14 ] has increased thanks to subsequent studies highlighting the dichotomy between solTNF and tmTNF and between their two TNF receptor subtypes. In particular, MS and EAE have been associated with harmful effects of solTNF via TNFR1 [ 163 , 164 , 165 ], while activation of oligodendroglial tmTNF/TNFR2 axis is capable to sustain oligodendrocyte maturation and remyelination [ 14 , 15 ] and to modulate the local inflammatory milieu by limiting detrimental microglial activation and immune cell infiltration from the blood circulation [ 166 ].…”
Section: Impact Of Microglia-derived Tnf On Brain Functionsmentioning
confidence: 99%